ANALISIS KEJADIAN KEBAKARAN DENGAN METODE “LOSS CAUSATION MODEL” PADA SEBUAH PABRIK KAYU LAPIS DI PACITAN - Evi Yunita Karuniawati; Bina Kurniawan; Hanifa Maher Denny (Jurnal Kesehatan Masyarakat (Undip), 2018)
Investigation of fire incident to find its cause is a repressive rule after the accident.The Loss Causation Model is one of the causal accident theories.The purpose of this research was to analyze a fire incident using "Loss Causation Model" method in a plywood factory of Pacitan Regency. This research was a qualitative research,conduct in-depth interviews with four main informants and two triangulation informants. The results of this study indicated that the Pacitan Plywood Plant has no standard and specific programs in preventing and preventing the fire hazard, it was reported that the condition triggered the emergence of basic cause in form of nonoptimal emergency preparedness. Hazardous conditions at risk of fire occurrence arising from physical or mechanical processes that cause contact between combustible materials, burning furnaces and excessive heating. The impact of fire incident affects workers, materials, production processes and working hours. The fire extinguishers and water tank were available but no accident analysis was conducted after the accident.